Hospital wastewater treatment reduces NDM‐positive bacteria being discharged into water bodies. (19th October 2019) - Divyashree, Mithoor; Mani, Madhu K.; Shama Prakash, Kabekkodu; Vijaya Kumar, Deekshit; Veena Shetty, Alandur; Shetty, Avinash K.; Karunasagar, Indrani
Abstract: New Delhi metallo‐β‐lactamase‐1 (NDM‐1) is a novel type of metallo‐β‐lactamase (MBL) associated with Enterobacteriaceae constitutes an important growing public health threat. The present study aims to characterize the NDM‐1 producing Gram‐negative bacteria (GNB) from the effluents of two tertiary care hospitals in Mangalore, South India and to profile their antibiotic resistance pattern. A total of 134 GNB were isolated from 30 hospital wastewater samples (treated and untreated) and analyzed. High‐level resistance among untreated effluent sample was found toward nalidixic acid (74.52%), followed by cefotaxime (72.64%) and ampicillin (66.03%). Among the treated effluent isolates, the high resistance was found toward ampicillin (85.71%) followed by cefotaxime (85.71%) and piperacillin–tazobactam (53.57%). From untreated effluent isolates, 9 were NDM‐1 positive by PCR; no isolates from treated effluent samples harbored bla NDM‐1 . Untreated hospital wastewater is found to be important reservoirs of antibiotic‐resistant bacteria carrying bla NDM‐1, and the presence of such bacteria in the effluents is a matter of great concern because they can contribute the antibiotic resistance to the natural environment. However, the absence of NDM in treated effluents emphasizes the importance of effluent treatment in reducing the dissemination of antibiotic‐resistant bacteria. Practitioner points: Hospital wastewater is the important reservoir of antibiotic‐resistant bacteria especially metallo‐β‐lactamase producers (NDM‐1). Wastewater treatment procedures in hospitals reduce the NDM isolates in the treated effluent. Thereby reduces the risk of resistance spread in the environment. Abstract : The treated and untreated wastewater samples from the tertiary care hospitals were genotypically characterized for the presence of the metallo‐β‐lactamase gene. bla NDM‐1 was detected in untreated effluent, but not in treated effluent. Hence the data shows that effluent treatment reduces discharge of bla NDM‐1 into the environment.